Komunikacja w stałym kręgu nadawczo-odbiorczym na materiale wybranych protokołów cechowych = Communication in a constant sender/receiver configuration: A study of selected guild protocols - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses communication in a constant sender/receiver configuration in the eighteenth century. The study was conducted on the material from protocols contained in the guild book of Krakow brewers. In a stable, mature speech community of brewing confraternities a constant sender/receiver configuration emerged.
Keywords: komunikacja; protokoły cechowe; selekcja informacji; redundancja; communication; guild protocols; selection of information; redundancy